EDUKASI ANEMIA DEFISIENSI BESI SEBAGAI DETEKSI DINI RISIKO PADA IBU HAMIL DI KECAMATAN MLATI, SLEMAN, YOGYAKARTA: Anemia Defisiensi Zat Besi, Deteksi Dini, Ibu Hamil - Chici Riansih; Aglita Janis Rupita (Permata Indonesia, 2023)
Pregnant women suffering from iron deficiency anemia can have a negative impact on the healthof mothers and babies born so that it can increase maternal mortality and infant mortality rates.The main cause of anemia during pregnancy is iron deficiency. Anemia is a global problem,especially for pregnant women. The main cause of anemia in pregnancy is iron deficiency followedby folate deficiency. WHO estimates that the incidence of anemia is around 42% in pregnantwomen with middle to lower economic conditions. Proper implementation of anemia is veryimportant, so that the interventions provided are accurate and improve services. The purpose ofthis community service activity is to increase the knowledge of pregnant women in early detectionof risks in their pregnancy. This form of activity is community service with educational methods,namely lectures and questions and answers. . The assessment of pregnant women'sunderstanding of iron deficiency anemia education as an early detection of risk in pregnant womenis 3 stages, namely the pretest stage, the education stage, and the postetest stage as well as theevaluation of deficiency anemia so that it gets treatment as soon as possible. The quality of thisgeneration of peneur begins from the time it is still in the womb to the first 1000 days of life.Responsibility starts with us caring and understanding.